A techno-economic comparison of CST and conventional cooking technologies in West Africa - Hussaini, Zaharaddeen Ali; Karim, Mounia; Ibrahim, Khalifa Aliyu; Luo, Zhenhua; Sansom, Christopher L.; Gurler, Tugba; Okeniyi, Johnson; Akraka, David; Ali, Saifullah (TIB Open Publishing, 2025)
Clean and affordable cooking remains a critical challenge in sub-Saharan Africa, where traditional biomass-based methods create health, environmental, and economic burdens. This study compares the economic viability of Concentrated Solar Thermal (CST) cookers, Fresnel Lens and Parabolic Trough Collector (PTC), with traditional charcoal stoves in rural Nigeria and Ghana using the Levelized Cost of Cooking a Meal (LCCM). While charcoal stoves offer the lowest short-term cost ($0.07628/meal), CST cookers become more economical over time, with the Fresnel Lens achieving an LCCM of $0.1432/meal over a 30-year lifespan. The PTC offers flexibility but has a higher cost due to its advanced design. The study emphasizes the potential health and environmental benefits of CST cookers, along with policy recommendations for overcoming adoption barriers through subsidies and innovative financing.
Keywords: 4206 Public Health; 42 Health Sciences; 3 Good Health and Well Being